Analysis of Factors Influencing Mother's Behavior in Providing Complete Foods and Breastfeeding Practices to Children Aged 6-12 Months in Prevention of Stunting - Noviana, Ulva; Hasinuddin, M.; Haris, Mustofa; Ekawati, Heni (GLOBAL HEALTH SCIENCE GROUP, 2024)
Providing additional food that is not targeted and does not comply with consumption rules can cause nutritional problems.Based on a preliminary study at the Jaddih Community Health Center, it was found that 60% of MP-ASI provision was in the deficient category and breastfeeding practice was 50% in the deficient category. This shows the low level of maternal behavior in providing MP-ASI and breastfeeding practices in preventing stunting.. Objective: This study aims to analyze the factors that influence maternal behavior to prevent stunting, namely attitudes, subjective norms, perceived control, intentions towards providing complementary breast milk and breastfeeding practices in children aged 6-12 months according to the Theory Planned Of Behavior Method: This type of researchis an analytical observational with a cross sectional approach.The population was 144 mothers who had babies aged 6-12 months, withA sample of 122, using purposive sampling technique.Independent variables (attitudes, norms, control, intentions, and behavior) and dependent variables (stunting prevention in providing MP-ASI and breastfeeding practices). Results: The research results of multiple linear regression tests on attitude variables with an intention p value of 0.001<(0.05), H0 is accepted, there is no significant relationship. Subjective norm variable with an intention p value of 0.829>(0.05). H0 is accepted, there is no significant relationship. Perception control variable with an intention p value of 0.004<(0.05). H1 is accepted, there is a significant relationship. Attitude variables, subjective norms, perceived control with intention p value 0.001 <(0.05) of the 3 variables above are simultaneously related. The results of the Spearman rank test for the attitude variable with intention obtained a p value of 0.000 <(0.05). H0 was rejected, there is a significant relationship between intention and behavior, the value r: 0.538 has a strong relationship. Conclusions: Mothers with high intentions have good behavior. This is a factor that influences mother's behaviorin complementary feeding and breastfeeding practices.It is hoped that health workers and those who work in service facilities can contribute to reducing the prevalence of stunting by increasing maternal preventive behavior for babies aged 6-12 months.